Non-crystalline films for device structures - Francombe, Maurice H. (Thin films (San Diego, Calif.), 2002)
Physics of Thin Films is one of the longest running continuing series in thin film science, consisting of 25 volumes since 1963. The series contains quality studies of the properties of various thin films materials and systems. In order to be able to reflect the development of today's science and to cover all modern aspects of thin films, the series, starting with Volume 20, has moved beyond the basic physics of thin films. It now addresses the most important aspects of both inorganic and organic thin films, in both their theoretical and their technological aspects. Volume 29 consists of chapters pulled from Hari Singh Nalwa's forthcoming Handbook of Thin Film Materials (ISBN: 0-12-512908-4). The chapters were selected because they deal exclusively with amorphous film structures and because they have a common relevance to semiconductor, or electronic, devices and circuits. These are subjects not yet stressed in the Thin Films series.